A Comprehensive Study on Production Efficiency Enhancement Using Optimal Power Press Tonnage in Stamping - Sukarman; Taufik Ulhakim, Muhamad; Khoirudin, Khoirudin; Mulyadi, Dodi; Amir, Amir; Suhara, Ade; Rahdiana, Nana (Jurnal Teknik Mesin Mechanical Xplore, 2024)
The use of press machines in stamping is an important aspect of the manufacturing industry, especially in producing efficient and quality components. This article aims to analyze the cost of the stamping process using mild steel SPCC-SD material measuring 200 mm x 25 mm x 0.8 mm, using two types of press machines, namely 80 tons and 40 tons. Through the cost analysis method, the total cost of the stamping process for the 80-ton press machine is Rp 16,417.4 per 10 pcs, while for the 40-ton press machine, it is Rp 15,028.5, indicating the cost efficiency of the 40-ton press machine is around 8.5%. The tonnage calculation shows that the 40-ton press machine is adequate for the blanking process, with a tonnage requirement of 4 tons, far below the available capacity. These results provide recommendations for the use of 40-ton press machines in the production of steel components on a small to medium scale, considering cost efficiency and optimal performance. This work is expected to increase productivity and cost efficiency in the manufacturing industry, especially at PT GA.